Testing the Job Demands-Resources Model for Nigerian Prison Staff Job Involvement. Issue 4 (8th August 2022) - Otu, Smart E.; Lambert, Eric G.; Elechi, O. Oko
ABSTRACT: The current study sets out to examine the effects of job demands and job resources on the job involvement of Nigerian correctional services staff. Job demands make the job more difficult and reduce positive work outcomes such as job involvement. Job resources make the job more pleasant and aid employees in doing their work, leading to increases in positive work outcomes, such as job involvement. Ordinary least squares (OLS) regression analysis of survey data from 120 correctional staff in a medium-security correctional center provides partial support for the job demands-resources model on job involvement for Nigerian correctional staff, with job resources showing greater effects than job demands in building job involvement. Specifically, the job demand variables were fear of victimization on the job and role overload, and the job resource variables were job variety, quality training, and job autonomy. Quality training and job autonomy had statistically significant effects on job involvement in a multivariate OLS regression analysis. Fear of victimization, role overload, and job variety had nonsignificant effects in the regression analysis.